The Influence of Islamic Religious Education in Shaping the Al-Karimah Morals of Students in Mulia Tanjung Sari Medan - Salim, Agus (Cattleya Darmaya Fortuna, 2023)
This study raises the issue of the role of learning Islamic Religious Education in forming the Morals of Santri Al-Karimah. The subjects in this study were class VIII students of TANJUNG SARI MUIA in March 2022. This type of research is field research, namely research where data collection is obtained by writing. This research was conducted in Kaksi Village, Tapung Hulu District, Kampar Regency. But more specifically, it was carried out at the MULIA TANJUNG SARI school. The research subjects were school principals, deputy principals, curriculum department, PAI teachers and students. While the method of data collection that is done by writing is observation, interviews and documentation. the data that has been collected by observation, questionnaire, and assignment methods. The results of this study indicate that the learning process at MULIA TANJUNG SARI runs quite well and effectively according to the basic concept of the learning process carried out by educators in general, namely students following the learning process of Islamic Religious Education with enthusiasm for the subject . The learning methods used by teachers of Islamic education at MULIA TANJUNG SARI include: lecture methods, discussion methods, question and answer methods, assignments. However, the results of observations and observations made in this study were not as expected. Even though the implementation of PAI in schools has been going according to plan, this student's al-karimah character is still in the less category.